Rancang Bangun Sistem Informasi Manajemen Pendidikan Pada Rumah Qur’an Berbasis Web Dengan Implementasi Role-Based Access Control - Mindy Atikah Chiara Gyver; Marhaeni Marhaeni; Hermin Arrang (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
Internet information technology is an information medium that is effective and efficient in disseminating information that can be accessed anytime and anywhere. But the internet also comes with several negative sides, one of which is the crime of data theft. Therefore, information sources are needed to support activities, including the Al Mukhlisin Qur'an House which requires an information system. This application will be created using the PHP programming language version 8.0 using the Laravel 9 framework and Postgresql as the database. Apart from that, the Role-Based Access Control concept will also be implemented to ensure that each menu available in this information system application can only be accessed by the type of user who has access. The method that will be used in the design process of the Qur'an house information system is the Waterfall method. This application will be a place to store data such as teacher assessment data for students and proof of transfer of students' infaq and sodaqoh payments which is expected to facilitate data access for users based on each user's access rights. Keywords : Education Management Information System, Role-Based Access Control, PHP, Laravel 9, Postgresql